Environmental Protection: Leading by Example - Vázquez-Cueto, María José; Asián-Chaves, Rosario; Camacho-Peñalosa, Enriqueta; Masero-Moreno, Inmaculada (Revista de Estudios Andaluces, 2017)
The attention and care to the environment is an agreed and consensus worry and, apart from generational interests, probably it is because it belongs to everyone, it affects to everyone and it concerns to everyone. The citizenship usually receives with claimed enthusiasm and they answer positively to the initiatives that promote good environmental behaviors. However, this good theoretical predisposition weakens on having known the expenses associated with the recovery and maintenance of the environment, especially when the citizens become aware of the direct repercussion for their pocket. This work reveals the discrepancy between the environmental worry and the money they are willing to pay to relieve the above-mentioned worry. It tries to put price to the environmental concern and for these reasons the take references from the Andalusian population. With the analysis of the information provided by the Andalusian Ecobarometer (EBA) and the Social Reality Survey in Andalusia (ERSA) we could observe the limited materialization in Euros of the high environmental worry, finding that the analyzed population is very far from preaching with the example and that it gives a void value to his environmental conscience. We have also made the analysis separately for different sex finding unlikeness by gender, that, even if they are small, they ought to be mentioned.